Unveiling the Nexus: Exploring Service Quality’s Impact on Student Satisfaction and Loyalty in Higher Education - Arizal N.; Wita Dwika Listihana (Recent Research Advances in Arts and Social Studies Vol. 9, 2024)
The purpose of this research is to empirically examine and analyze the influence of Service Quality on Satisfaction and its impact on Student Loyalty. This study adopts a descriptive (survey) method with a quantitative approach design. The data used consists of primary and secondary data. The population in this study is students of the Faculty of Economics at Lancang Kuning University, with a sample size of 100 individuals adopting Slovin’s proposition. The sampling technique used is non-random sampling with the Accidental Sampling method. Data analysis is conducted using Structural Equation Modelling (SEM) with the Warp PLS application. The research results indicate that there is a significant influence of the physical, reliability, and assurance dimensions on customer satisfaction, whereas responsiveness and empathy aspects are not significant. The satisfaction variable has a significant influence on loyalty. The research results also show that all dimensions and variables have positive relationships, both from the perspective of service quality on satisfaction and satisfaction on loyalty.